2012
DOI: 10.1111/j.1708-8208.2012.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Initial Soft Tissue Thickness on Peri‐Implant Bone Remodeling

Abstract: The present study suggests that implants with lower abutments, reflecting the initial gingival thickness, lose more peri-implant bone, possibly by a re-establishment of the biological width.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
138
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(168 citation statements)
references
References 37 publications
23
138
5
2
Order By: Relevance
“…16 In the present study, group 3 (with an abutment height of ≥3 mm) showed reduced MBL, although the distance from the alveolar bone crest to the gingival margin would be >4 mm. 16 In the present study, group 3 (with an abutment height of ≥3 mm) showed reduced MBL, although the distance from the alveolar bone crest to the gingival margin would be >4 mm.…”
Section: Resultscontrasting
confidence: 42%
See 1 more Smart Citation
“…16 In the present study, group 3 (with an abutment height of ≥3 mm) showed reduced MBL, although the distance from the alveolar bone crest to the gingival margin would be >4 mm. 16 In the present study, group 3 (with an abutment height of ≥3 mm) showed reduced MBL, although the distance from the alveolar bone crest to the gingival margin would be >4 mm.…”
Section: Resultscontrasting
confidence: 42%
“…15,16 In the present study, group 1 showed a low success rate and an increased mean MBL. 15,16 In the present study, group 1 showed a low success rate and an increased mean MBL.…”
Section: Resultscontrasting
confidence: 40%
“…21 In the present study, the vertical position of the implant was adapted according to soft tissue thickness and a uniform final abutment of 4 mm height was chosen. After implant placement, an initial bone remodeling occurs resulting in steady-state bone levels after 3 to 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Beside the difference in implant surface, the two implants are identical with a thread pitch of 0.6 mm, an integrated platform-shift with a smooth implant bevel, and an internal connection and microthreads on the implant neck. 21 After final implant seating, insertion-torque values were registered on the drill unit (W&H Dentalwerk, Bürmoos, Austria). The implants were placed crestally or subcrestally, taking the soft tissue thickness into account, ensuring a 3-4 mm soft tissue seal ( Figure 1C).…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…10 Therefore, crestal bone preservation is paramount for implant success. 12,13 Another factor that affects this crestal bone remodeling is the microgap at the implant-abutment junction. This biological phenomenon is referred to as "biological width" and is considered to be a physiological process.…”
mentioning
confidence: 99%